Laparoscopic cholecystectomy in situs inversus totalis: a case report - Blake Geoffrey; McKay Damian (BMC Surgery, 2005)
Abstract Background Laparoscopic cholecystectomy is one of the commonest surgical procedures carried out in the world today. Occasionally patients present with undiagnosed situs inversus and acute cholecystitis. We discuss one such case and outline how the diagnosis was made and the pitfalls encountered during surgery and how they were overcome. Case presentation A 32 year old female presented to our department with epigastric pain radiating through to the back. A diagnosis of acute cholecystitis in a patient with situs inversus totalis was made following clinical examination and radiological investigation. Laparoscopic cholecystectomy was subsequently performed and the patient made an uneventful recovery. Conclusion Situs inversus presenting with acute cholecystitis is very rare. The surgeon must appreciate that care should be taken to set up the operating theatre in the mirror image of the normal set-up for cholecystectomy, and that right handed surgeons must modify their technique to adapt to the mirror image anatomy.